Intervenções de recuperação no Centro Histórico de João Pessoa: bairro do Varadouro - Cavalcante, Roberta Paiva (2009)
Based on the process of revitalization and rehabilitation of degraded or abandoned stretches that have been developed around the world since the end of the 20th century, this research is aimed to evaluate the process of revitalization of Historic Centre of João Pessoa, choosing as a target the Bairro do Varadouro and performing the evaluation of three proposals within it: the Project for Revitalization of Varadouro and Porto do Capim, the Project Moradouro and Revitalization of Praça Anthenor Navarro. From these goals, some existing urban issues within Historic Centre of João Pessoa have been noticed, where some appears as a consequence of the proposed revitalization itself. We used, for the evaluation of urban space, sector quality criteria (land use, configuration space, road system and parking, spaces, activities and urban furniture), therefore revealing them as important points of discussion on urban transformations ( positive and negative) that the processes of revitalization / rehabilitation take in historic places in João Pessoa. This study presents a description of each proposal, with its objectives and possible consequences within the urban spaces, concluding that, due to the large number of variables inside of it, the scope of a feasible plan must show the needs in all levels of intervention, such as to tourism (culture and recreation) and services and trade of the housing sector, which should cover all existing social issues.